2020
DOI: 10.1111/anae.15313
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID‐19 on general anaesthesia rates for caesarean section. A cross‐sectional analysis of six hospitals in the north‐west of England

Abstract: Summary At the onset of the global pandemic of COVID‐19 (SARS‐CoV‐2), guidelines recommended using regional anaesthesia for caesarean section in preference to general anaesthesia. National figures from the UK suggest that 8.75% of over 170,000 caesarean sections are performed under general anaesthetic. We explored whether general anaesthesia rates for caesarean section changed during the peak of the pandemic across six maternity units in the north‐west of England. We analysed anaesthetic information for 2480 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 21 publications
6
54
6
2
Order By: Relevance
“…A nationwide questionnaire survey in Turkey demonstrated that 62.1% of the responders stopped elective surgeries after the first case was reported in Turkey (11 March 2020) [ 13 ]. A cross-sectional analysis in northwest England reported that the general anesthesia rates for cesarean section were significantly reduced from 7.7% to 3.7% due to the COVID-19 pandemic [ 14 ]. The largest, latest nationwide survey from the COVIDSurg group showed that 72.3% of surgeries were canceled or postponed during the 12-week peak of disruption caused by the COVID-19 pandemic [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide questionnaire survey in Turkey demonstrated that 62.1% of the responders stopped elective surgeries after the first case was reported in Turkey (11 March 2020) [ 13 ]. A cross-sectional analysis in northwest England reported that the general anesthesia rates for cesarean section were significantly reduced from 7.7% to 3.7% due to the COVID-19 pandemic [ 14 ]. The largest, latest nationwide survey from the COVIDSurg group showed that 72.3% of surgeries were canceled or postponed during the 12-week peak of disruption caused by the COVID-19 pandemic [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bhatia et al. analysed anaesthetic information for 2480 caesarean sections across six maternity units from April to July 2020 (during the first wave of the pandemic in the UK) [21]. They compared it with data from 2555 caesarean sections performed at the same hospitals over a similar period in 2019.…”
Section: Anaesthetic Practice In Maternity Care During the Covid‐19 Pmentioning
confidence: 99%
“…Although the clinical characteristics of COVID-19 parturients is similar with non-pregnant COVID-19 patients (Allotey, Stallings et al, 2020), COVID-19 results in additional challenges for perioperative management in parturients (Zheng, Hebert et al, 2020) and the outcomes of maternal and fetal appeared barely satisfactory (Yu, Li et al, 2020). Based on clinical practices and expert opinions, neuraxial anaesthesia in preference to general anaesthesia for caesarean delivery in COVID-19 parturients (Bhatia, Columb et al, 2020). However, more attention should be focused on neuraxial anaesthesia-related hypotension in COVID-19 parturients.…”
Section: Introductionmentioning
confidence: 99%